Effects of environmental conditions on feeding behavior in beef cattle in an intensive system in the Sinú Valley (2012)
Increases in temperature and relative humidity together with the solar radiation effect are detrimental to animal welfare, affecting their behavior when it comes to feeding and digestive behavior, which affects their productivity. Therefore, the goal of this research was to analyze the link between atmospheric variables, air temperature, relative humidity, wind speed and solar radiation to the time of grazing and rumination of commercial Zebu cattle. The research took place from July to October 2010, at the Turipaná Center, Corpoica (Cereté, Colombia). Male intact bovines (27), with an average weight of 314 ± 29 kg, grazed in an area of 18 hectares, established with Panicum maximum cv. Mombasa, Cynodonnlem fluensis and Brachiaria hybrid cv. Mulato II, without shade availability. Eight evaluations were conducted for 8 days in the experimental period for atmospheric variables and ingestion. Notes were taken in 12 hour time frames (6:00 AM a 6:00 PM). The outcome showed that as the air temperature, relative humidity and solar radiation increased, the grazing time decreased and rumination time lasted longer. However, when wind speed increased, grazing time increased as well and rumination took less time. The results showed that the air temperature, relative humidity, solar radiation and wind speed had a direct influence on the ingestive behavior of beef cattle managed in intensive systems (shadeless) in Valle del Sinú.